The mitogen-activated protein kinase ERK5 regulates the development and growth of hepatocellular carcinoma. Issue 9 (2nd September 2014) - Rovida, Elisabetta; Di Maira, Giovanni; Tusa, Ignazia; Cannito, Stefania; Paternostro, Claudia; Navari, Nadia; Vivoli, Elisa; Deng, Xianming; Gray, Nathanael S; Esparís-Ogando, Azucena; David, Ezio; Pandiella, Atanasio; et al.
Abstract : Objective: The extracellular signal-regulated kinase 5 (ERK5 or BMK1) is involved in tumour development. The ERK5 gene may be amplified in hepatocellular carcinoma (HCC), but its biological role has not been clarified. In this study, we explored the role of ERK5 expression and activity in HCC in vitro and in vivo. Design: ERK5 expression was evaluated in human liver tissue. Cultured HepG2 and Huh-7 were studied after ERK5 knockdown by siRNA or in the presence of the specific pharmacological inhibitor, XMD8-92. The role of ERK5 in vivo was assessed using mouse Huh-7 xenografts. Results: In tissue specimens from patients with HCC, a higher percentage of cells with nuclear ERK5 expression was found both in HCC and in the surrounding cirrhotic tissue compared with normal liver tissue. Inhibition of ERK5 decreased HCC cell proliferation and increased the proportion of cells in G0/G1 phase. These effects were associated with increased expression of p27 and p15 and decreased CCND1. Treatment with XMD8-92 or ERK5 silencing prevented cell migration induced by epidermal growth factor or hypoxia and caused cytoskeletal remodelling. In mouse xenografts, the rate of tumour appearance and the size of tumours were significantly lower when Huh-7 was silenced for ERK5. Moreover, systemic treatment with XMD8-92 of mice with established HCC xenografts markedly reduced tumour growth and decreased the expression of the proto-oncogene c-Rel. Conclusions: ERK5 regulates the biology of HCC cells and modulates tumour development and growth in vivo. This pathway should be investigated as a possible therapeutic target in HCC.